STRATEGI KOMUNIKASI SATUAN LALU LINTAS (SAT LANTAS) KEPOLISIAN RESORT KOTA (POLRESTA) PEKANBARU DALAM MENSOSIALISASIKAN “SAFETY RIDING” - Harun Al Rasyid; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The level of traffic violations in Pekanbaru increasingly rising. Traffic violations consist of 21493 was given a speeding ticket and 6713 given a reprimand in 2014, whereas in 2015 increased significantly, namely; 11403 27 788 was given a speeding ticket and given a reprimand against violators of traffic in the city of Pekanbaru. In an effort to reduce abuse and raise public awareness of Pekanbaru in driving safe, orderly and peaceful course, is inseparable from the role of communication a more active and effective. The strategy used by the Satuan Lalu Lintas (Sat Lantas) Kota Pekanbaru include preventive strategy being pursued is to disseminate "Safety Riding" through publications in mass media, electronic and print media. This research using qualitative descriptive methods and data collection techniques are grouped by the fact the field through observation, interviews and documentation. Informants in this study consists of 4 people who were taken by purposive sampling technique. Interactive data analysis model the author uses to describe the results of research into techniques for data analysis and data validity checking researchers used a technique extension of participation and triangulation. The results showed that the communication strategy Satuan Lalu Lintas (Sat Lantas) Kota Pekanbaru targeted in disseminating Safety Riding is the entire community of Pekanbaru which have private vehicles, especially two-wheelers and the placement of the target is divided into five segments. Groups of institutions / agencies, groups of motorcycle clubs, youth groups, children and the general public. After the use of the media are divided into media groups and the mass media so that it can reach the whole community. The contents of the message delivered by the Satuan Lalu Lintas (Sat Lantas) Kota Pekanbaru are persuasive message, educative and informative. In doing various activities to socialize Safety Riding. Strategy communicator doing by Satuan Lalu Lintas (Sat Lantas) Kota Pekanbaru by selecting a few volunteers as extended of Satuan Lalu Lintas (Sat Lantas) Kota Pekanbaru to socialize Safety Riding to the public but not in all segments, only the segment motorcycle club, child, and teenagers.Keywords: communication strategy, sosializing, safety riding